The Influence Of Product Innovation, Process Innovation, Marketing Innovation and Bookkeeping On Bread & Cake SMEs Business Performance in Payakumbuh - Marlina, Winny Alna (Politeknik Negeri Bengkalis, 2023)
The goal of this study is to ascertain how product innovation, process innovation, marketing innovation, and bookkeeping innovation affect the business performance of the Bread & Cake MSME in Payakumbuh City. This approach to research is quantitative. This study employed primary data and a research tool that included a survey provided to owners of MSMEs that make bread and cakes in Payakumbuh City. Non-probability sampling using a straightforward random sample approach is the sampling methodology. SmartPLS 3 software is used in this study's data processing. E-wom and advertising are two of the dimensions of the marketing innovation variable. According to the study's findings, product innovation has little impact on business success, but process innovation, marketing innovation, and bookkeeping innovation do. So, although advertising has no impact on marketing innovation, E-wom has a positive impact on it.